From spectra to atmospheres: solving the underconstrained retrieval problem for exoplanets. Issue Volume 8:Issue S299(2013) (6th January 2014) - Barstow, Joanna K.; Aigrain, Suzanne; Irwin, Patrick G. J.; Bowles, Neil; Fletcher, Leigh N.; Lee, Jae-Min
Abstract: Spectroscopic observations of transiting exoplanets have provided the first indications of their atmospheric structure and composition. Optimal estimation retrievals have been successfully applied to solar system planets to determine the temperature, composition and aerosol properties of their atmospheres, and have recently been applied to exoplanets. We show the effectiveness of the technique when combined with simulated observations from the proposed space telescope EChO, and also discuss the difficulty of constraining a complex system with sparse data and large uncertainties, using the super-Earth GJ 1214b as an example.